New Approach for Evaluation of Electromagnetic Properties of Three- Phase Windings - Bukšnaitis, J. (Elektronika ir Elektrotechnika, 2007)
A new approach for evaluation of electromagnetic properties of three-phase windings is presented, on the basis of which it is easy to compare different type windings of different parameters and to determine the optimal one. It is offered to evaluate momentary space no sinusoidal rotating magnetomotive force value using distortion factors or electromagnetic efficiency factors, which are calculated using the results of harmonic function analysis. The optimal values of both factors are equal to one. It was determined, that in order to evaluate electromagnetic properties of three-phase windings it is better to use electromagnetic efficiency factors than distortion factors. Ill. 7, bibl. 6 (in English; summaries in English Russian and Lithuanian).